The Burden of Likely Rubella Infection among Healthy Pregnant Women in Abakaliki, Ebonyi State, Nigeria - Ekuma, Uchechukwu Onyeukwu; Ogbu, Ogbonnaya; Oli, Angus Nnamdi; Okolo, Martin-Luther Oseni; Edeh, Peter Anyigor; Al-Dahmoshi, Hussein O. M.; Akrami, Sousan; Saki, Morteza (Interdisciplinary Perspectives on Infectious Diseases, 2022)
The first 140 days of pregnancy are critical as regards rubella virus infection because of the likelihood of a poor pregnancy outcome. This study was undertaken to investigate the likelihood of exposure to poor pregnancy outcomes due to seroprevalence of rubella among selected pregnant women attending Mile Four Hospital, Abakaliki, Ebonyi State, Nigeria. The seroprevalence of rubella immunoglobulin M (IgM) antibodies was investigated among pregnant women. A total of 187 sera samples collected from the women were screened for rubella virus IgM antibody using the enzyme-linked immunosorbent assay (ELISA). The results obtained were analyzed using SPSS. The chi square test was performed at a P value of 0.05 significance and at a 95% confidence interval. Of the 187 pregnant women, 35 (18.72%) were positive for the rubella virus. Pregnant women within 26–30 years of age had the highest prevalence (26.15%), while those aged 35–40 years had the least prevalence. Married women had the highest prevalence (20.0%), followed by singles (16.67%) and widows (15.38%), while divorced pregnant women recorded the least prevalence (9.20%). Pregnant women with no formal education were more predisposed to rubella virus (22.22%) infection compared to their educated counterparts. Occupationally, full-time housewives had the highest prevalence (24.26%). The infection rates seemed to wane as pregnancy advanced. The first trimester had the highest prevalence (21.88%), followed by the second trimester (18.84%) and the third trimester (17.44%). Pregnant women living in urban areas had higher IgM seroprevalence (20.18%) than those in rural areas (16.67%). Furthermore, grand multigravidas were more infected (22.73%) than primigravidas (14.52%) and multigravidas (20.39%). The seroprevalence of rubella in this study was high, and it calls for general surveillance and mass immunization of children and females of childbearing age in the area to help reduce the incidence of congenital rubella syndrome.